Explicit mathematical models of multiple polarization-measurements and the Einstein-Bohr debate - Hess, Karl; Jakumeit, Jürgen (Frontiers in Quantum Science and Technology, 2025)
We present mathematical models that also may be formulated as computer models for experiments that feature single photon resolution and multiple pairs of polarizers to determine the sorting into ordinary and extraordinary channels. The models are based on Einstein’s hypothesis of elements of physical reality that determine the photon properties and are at first developed for Malus-type experiments. It is then shown that analogous models apply to the well-known Clauser-Aspect-Zeilinger experiments and violate all Bell-type inequalities without violating Einstein’s separation principle. The Bell-type inequalities do not apply to the actual experiments, because they cannot obey the physically necessary symmetry with respect to polarizer-pair rotations. We believe that these findings suggest a change of current interpretations of quantum entanglement away from instantaneous influences at a distance, as promoted in the physics Nobel-lectures 2022, and back toward Einstein’s ideas as well as the more recent ideas of Gerard ‘t Hooft.